International Meeting 40 Years of the 1980 Azores Earthquake, online meeting, 6-7 October 2020 - Oliveira, C. S. (2020)
It is our great pleasure to organize the 40 Years of the 1980 Azores Earthquake (40|80) that will be held online between 6th and 7th October 2020. As we move the 40|80 completely online, we look forward to offering you the same vibrant programming, impactful networking, and opportunities to reflect and connect over the emerging and salient topics in our field. The theme of the 40|80 is to remind the 40 years of a devastating earthquake that affect mainly Terceira Island but also Graciosa and São Jorge Island. At 40|80, we would promote a state-of-the-art of the seismicity in general but also topics like volcanic seismicity, tsunamis, historical seismicity, crustal deformation, tsunamis, seismic hazard and risk. Since earthquakes cause economic and social losses, topics like case studies on the rehabilitation of buildings, retrofit techniques of heritage monuments, an overview of Eurocodes and construction codes, social and economic aspects are paramount to understand their impact and how to mitigate them. Thus, we would like at 40|80 to provide the time and place where attendees from around the world can share their experience and knowledge to build disaster-resilient societies and to create new directions through integrating various fields The virtual meeting of 40|80 will include sessions and keynotes.